Notes on meromorphic functions with positive coefficients defined by Bessel function - Venkateswarlu, Bolineni; Reddy, Pinninti Thirupathi; Yalcin, Sibel; Settipalli, Sridevi (Penerbit Universiti Kebangsaan Malaysia, 2022)
In this article, a new subclass of univalent meromorphic under Bessel mapping function is defined. Some properties such as coefficient estimates, starlikeness and convexity radii, and extreme points are derived. Finally, partial sums and neighbourhood properties are given.